Effect of the Re-Vitrification of Embryos at Different Stages on Embryonic Developmental Potential - Li, Jingyu; Xiong, Shun; Zhao, Yanhua; Li, Chong; Han, Wei; Huang, Guoning (Frontiers in Endocrinology, 2021)
Background Using re-vitrified human embryos for frozen-warmed embryo transfer (FET) is a valuable option when there are no other cryopreserved embryos to use, however, except for the PGT cases, no published data are available for FET with human embryos that were re-vitrified at different developmental stages. Objective To evaluate the effect of re-vitrification of embryos at different stages on embryonic developmental potential. Method This study included clinical retrospective and mouse experimental studies. For the retrospective study, a total of 25 FET cycles with re-vitrified day 3 embryos (re-vitrification group 1) and 54 FET cycles with re-vitrified day 5 blastocysts (re-vitrification group 2) between January 2015 and December 2019 were included in this study. The corresponding FET cycles with once-vitrified embryos were identified using propensity score (PS) matching according to the time of embryo transfer. For the mouse experimental study, we divided embryos into 5 groups: fresh (group 1), vitrified at the 8-cell stage (group 2), vitrified at the early blastocyst stage (group 3), vitrified at the 8-cell stage, and re-vitrified at the 8-cell (group 4) or early blastocyst stage (group 5). The fresh embryos was selected as control group. The primary outcome in this study was delivery outcomes. Results No significant difference in delivery rate was detected between re-vitrification group 1 (24.00%) and the corresponding control group (28.00%). However, re-vitrification group 2 (46.3%) showed a significant decrease in delivery rate compared with the two corresponding control groups (63.89% and 64.12%) (P < 0.05). Our experiment using mouse embryos also confirmed the clinical data, and showed that re-vitrification at the blastocyst stage following the first round of vitrification at the 8-cell stage reduced the delivery rate. In addition, both re-vitrified groups showed a significantly higher expression level of BAX. However, only re-vitrification at the blastocyst stage increased the expression level of CASPASE3. Conclusions Re-vitrification at the 8-cell and blastocyst stages has different effects on embryonic developmental potential, as re-vitrification at blastocyst stage following a previous vitrification at 8-cell stage reduced the delivery rate, while vitrification at the 8-cell stage twice achieved comparable pregnancy outcomes to the once-vitrified group.